Understanding the Mechanisms of Activity-based Workspaces: A Case Study. Issue 1 (January 2022) - Eismann, Tobias T.; Pakos, Oscar; Rücker, Marc; Meinel, Martin; Maier, Lukas; Voigt, Kai-Ingo
In recent years an increasing number of organizations have started to rethink their physical work environments and recognized the value of having activity-based workspaces (ABWs). This allows employees to choose freely between several work environments based on their specific task. There is growing debate amongst researchers about the effects of ABWs on employee behavior, but companies are still not aware of the options available or the consequences of moving to an ABW layout. This single-case, exploratory study uses 36 interviews and multiple data sources in a German organization leading in use of ABWs to generate insight into this topic. We develop a taxonomy of ABWs and analyze how various design parameters affect how people perform in ABWs regarding communication, leadership, working style, and work performance. We relate these findings to previous research and develop a cause-effects framework of ABWs. Against these findings, we generate recommendations for future research and practice.